Removal of cadmium and copper in aquatic environment by modified kaolinite - Khai, Nguyen Manh; Van, Le Anh; Anh, Pham Vy; Hien, Dinh Thi; Viet, Nguyen Hoang (Vietnam Journal of Chemistry, 2014)
The removal of Cd(II) and Cu(II) by kaolinite and its modified forms (by thermal or/and acid activation) in aqueous medium have been studied. Batch adsorption experiments were carried out with various pH values, interaction time and heavy metals concentration. The results showed that, the Cd(II) and Cu(II) adsorption of modified kaolinite was strongly affected by pH of medium. Initially, the rate of the adsorption was fast and then reached the maximum within 30 min of agitation for Cd(II) and Cu(II). The kinetic of adsorption was best described by second-order-mechanism. The amount of Cd(II) and Cu(II) adsorption at equilibrium, qe, were 2.1-2.6 and 2.1-2.5 mg.g-1, respectively. The second-order rate constant, k, of Cd(II) and Cu(II) adsorption were 0.12-0.37 and 0.27-1.47 g.mg-1.min-1, respectively. The adsorption data are good fit with Freundlich isotherm model. The Freundlich adsorption affinity were between 26.6 to 36.2 Ln.mg1-n.kg-1 for Cd(II), and between 6.7 to 14.4 Ln.mg1-n.kg-1 for Cu(II). The result indicated that kaolinite and its modified forms are good adsorbents for Cd(II) and Cu(II) in aqueous medium. Keywords: Cadmium, copper, removal, modified kaolinite